Reactivation of the Role of Pesantren for the Maslahah of the Ummah - Firdaus, Danang; Amin, Nasihun (FiTUA: Jurnal Studi Islam, 2025)
This study emerges from the observation that many pesantren remain predominantly focused on student care, limiting their broader social impact; this research reactivates the social role of pesantren by situating it within the normative framework of KH Sahal Mahfudh’s social fiqh. A qualitative literature-based approach was employed, drawing primarily on KH Sahal’s works and peer-reviewed journal articles, analyzed sequentially through open, axial, and selective coding, with library triangulation applied to ensure validity. Findings indicate that KH Sahal’s social fiqh prioritizes maqāṣid and basic needs fulfillment as practical instruments of ijtihād, enabling pesantren to develop integrated curricula, productive enterprises such as cooperatives and canteens, primary health services, vocational training, and environmental conservation programs. Implications call for institutional reform, enhanced methodological capacity among administrators, transparent waqf management, and supportive local policies to facilitate stakeholder partnerships. The study recommends comparative field testing of the proposed reactivation model. Systematic implementation is expected to improve social inclusion, reduce local economic disparities, and strengthen community resilience through women’s and youth participation alongside sustained monitoring and evaluation and institutional learning frameworks also.